Ischemic Stroke In infant With Tetralogy of Fallot - Dian Ayu Hamama Pitra; Lydia Susanti (Health and Medical Journal, 2019)
Objectives: Although stroke is often viewed as occurring primarily in the elderly, it also strikes infants, children, young adults. Stroke in children are rare but increasingly important conditions due to the severity of their complications and diverse diagnostic differentials. It is not yet clearly understood and with multifactorial etiologies. When it comes to stroke, children are not just little adults. Stroke risk factors, symptoms, prevention efforts, and treatment are often different in children than in adults. Up to 80 % of children with ischemic stroke have cardiovascular disease. Case report: RS, An infant, aged two and half years old was admitted to DR. M. Djamil hospital Padang, with right hemiplegy and developed aphasia after activity. One year ago, he had history of cyanotic skin but neglected by his parents and never sought medical treatment. Physical findings on this patient are cyanosis and clubbing fingers. Cardiac auscultation revealed a pansystolic murmur grade III-IV best heard at the upper left sternal border. Chest radiograph showed a characteristic “bootshaped” heart, which is a reflection of Right Ventricular (RV) hypertrophy. The ECG showed right axis deviation. Brain CT Scan revealed a large hypodense lesion on the left cerebral hemisphere suggested as large brain infarction. Echocardiogram revealed tetralogy of fallot with a larged malaligned ventricular septal defect (VSD) with 60 % aortic override. Patient was managed conservatively. After two weeks of admission, patient was discharged with improvement.Conclusion : Ischemic stroke in this infant with tetralogy of fallot occurred via paradoxical embolism mechanism.